MODELING ECONOMIC AGENTS’ EXPECTATIONS AS A TOOL OF FORECASTING SHORT-TERM ECONOMIC CYCLES - Leonid A. Elshin; Maxim V. Savushkin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article shows the necessity to develop, substantiate (verify) and test models of cyclic fluctuations of economy built on the basis of such factors, which could have high sensitivity to changes in external and internal environment of the economic system and possess high predictability of cyclic trends. The authors prove that a possible way to resolve the problem is to model economic agents’ expectations and identify trends of their economic development. On the basis of quantitative estimation of economic agents’ expectations they designed algorithm for diagnosing cyclic fluctuations of economy, which gives an opportunity to identify rising and declining phases of economic cycles with an advance lag of 1-2 years with the effective trajectory of economic development of national economy.